Inhibitory Effect of Polydatin Against Aeromonas hydrophila Infections by Reducing Aerolysin Production - Dong, Jing; Yan, Tianhui; Yang, Qiuhong; Zhou, Shun; Song, Yi; Liu, Yongtao; Ma, Liang; Xu, Ning; Yang, Yibin; Ai, Xiaohui (Frontiers in Veterinary Science, 2022)
The fast growing demands of aquatic products bring the rapid development of aquaculture. However, diseases caused by bacterial pathogens result in severe economic losses all over the world. Although the introduction of antibiotics to aquaculture decreased the mortality of infectious diseases, the emergence of antibiotic resistance caused treatment failure. Therefore, drugs with novel strategies are needed for combatting infections caused by resistant bacterial strains. In the present study, aerolysin was identified as a target developing drugs from natural compounds against Aeromonas hydrophila (A. hydrophila) Infections. We found that polydatin without inhibitory effect against A. hydrophila growth could decrease the hemolysis mediated by aerolysin. Western blot and qPCR assays demonstrated that the addition of polydatin decreased the production of aerolysin by down-regulating the aerolysin encoding gene. Moreover, cell viability and animal studies found that polydatin could reduce the pathogenesis of A. hydrophila both in vitro and in vivo. Taken together, these findings provided a novel approach and candidate in treating resistant A. hydrophila infections in aquaculture.